Involuntary Disclosures and Stakeholder-Initiated Communication on Social Media. (March 2023) - Dobija, Dorota; Cho, Charles H.; She, Chaoyuan; Zarzycka, Ewelina; Krasodomska, Joanna; Jemielniak, Dariusz
This study explores firm responses to stakeholder-initiated involuntary disclosures, which are disclosures made by stakeholders about an organization but are against the will of managers, and subsequent stakeholder reactions. We analyzed 134, 977 firm Twitter replies from seven companies to identify their responses to involuntary corporate social responsibility (CSR) disclosures and find that companies demonstrate different attitudes toward engagement in the exchange about involuntary disclosures. Whereas some companies communicate with stakeholders, others are almost silent. When a company engages in communication with its stakeholders, the communication is mostly one-way, and mortification or dissent is the likely response strategy. We also find that while stakeholders generally do not continue to engage with corporate communications, they are likely to respond when companies deny the information revealed by involuntary disclosure. Our results suggest that involuntary disclosures on social media are not able to improve communication between stakeholders and companies.